2015
DOI: 10.1002/tox.22194
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviated the toxic reaction of Rhizoma Paridis saponins in a 45-day subchronic toxicological assessment of rats

Abstract: Rhizoma Paridis saponins (RPS), as steroid saponins, are the main components in Paris polyphylla. Curcumin (diferuloylmethane) is the most important component in the spice turmeric. In our previous research, RPS exhibited side effects such as nausea, vomiting, diarrhea, and so forth. Combination with curcumin not only alleviated the toxicity and gastric stimulus induced by RPS, but also improved the quality life of mice bearing tumor cells and enhanced their anticancer effect. This study evaluated subchronic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Rhizoma paridis saponins (RPS) played a good anti‐tumour role in many clinical applications. Combination of RPS and CUR not only alleviated the toxicity and gastric stimulus induced by RPS, but also improved the quality life of mice bearing tumour cells and enhanced their anti‐cancer effect . In our previous research, PSII (formosanin C) as one of the main effective compounds in RPS was absorbed in rat plasma after oral administration of RPS .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizoma paridis saponins (RPS) played a good anti‐tumour role in many clinical applications. Combination of RPS and CUR not only alleviated the toxicity and gastric stimulus induced by RPS, but also improved the quality life of mice bearing tumour cells and enhanced their anti‐cancer effect . In our previous research, PSII (formosanin C) as one of the main effective compounds in RPS was absorbed in rat plasma after oral administration of RPS .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in our previous research, CUR not only alleviated the toxicity and gastric stimulus induced by RPS, but also improved the quality life of mice bearing tumour cells and enhanced their anti‐cancer effect . With the widely application of complex mixtures in clinic, the aim of this study was to investigate the synergistic anti‐cancer effects of PSII and CUR in lung cancer cell lines.…”
Section: Introductionmentioning
confidence: 97%
“…Acute toxicity test was performed as per OECD guideline 423 for testing of chemicals ( 2001) [5]. Healthy young adult rats, non-preg-nant female rats weighing about 150-200 g were administered only once orally at a single doses of 2000 mg/kg bw and 5000 mg/kg bw of ethanol extract of pirdot leaves, whereas the control group only received Na CMC 0.5%.…”
Section: Acute Toxicity Studymentioning
confidence: 99%
“…Secondary metabolites such as saponins and polyphenols can have adverse effects such as causing poisoning when overused. Polyphenols 0.5% -1% show hepatotoxic and nephrotoxic effects 4 and saponins can cause serious damage to the liver and kidneys 5 . Unexpected adverse effects of these secondary metabolites can occur due to increased Reactive Oxygen Species (ROS) in the body that will trigger the release of acrolein, malondialdehyde and 4-hydroxy-2nonenal, causing disruption of normal protein function which has an impact on changes in cell activity [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies had shown that curcumin could antioxidant, anti-inflammatory, anti-cancer, protected nervous system, controlled obesity, and diabetes. [11][12][13][14][15][16][17] Among them, curcumin had excellent antioxidant performance. Curcumin exerted antioxidant effect by regulating the expressions of superoxide dismutase (SOD), heme oxygenase 1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2), thus protecting the arteries and improving the arterial health.…”
Section: Introductionmentioning
confidence: 99%